Incidence and Progress of Vesicoureteric Reflux after Primary Fulguration of Posteriorurethralvalves (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: Posterior urethral valve (PUV) is the most frequent cause of urethral obstruction in male child. These lesions usually result in lifelong disabilities with incontinence and decreased renal function despite optimal medical management. Primary fulguration without upper tract diversion is the preferred modality of treatment in most cases of PUV. Regular follow-up is needed to check completion of valve fulguration, renal function, status of hydronephrosis, vesicoureteric reflux (VUR), urinary tract infection (UTI), and bladder function.Materials and methods: We conducted interventional study among 30 purposively selected patients of PUV in the Department of Pediatric surgery, Dhaka Medical College Hospital (DMCH), Dhaka, over a period of 20 months from December 2009 to July 2011. Age of study subjects varied from 2 days to 14 years. Among the 30 patients, 16 were children in the age group between 1year to14 years (53.3%), 11(36.7%) were infants and the rest 03(10%) were neonates. Most of the patients presented with weak urinary stream, dribbling of urine, straining at micturition, UTI and palpable bladder. All children were subjected to ultrasonography (USG), blood urea, serum creatinine, routine urine examination and culture studies. Structured questionnaire was used to collect information regarding improvement or disappearance of VUR and renal functional status before & after primary fulguration of PUV.Results: Average serum creatinine level was found gradually decreased in subsequent follow up in comparison with the previous one. This difference of creatinine level was found statistically significant in t-test (p